Recurrent massive bleeding from a small intestinal arteriovenous malformation after surgery for biliary atresia in an infant: a case report and literature review - Wataru Kudo; Katsunori Kouchi; Ayako Takenouchi; Aki Matsuoka; Kiyoaki Yabe; Tadao Nakazawa; Atsuko Hasegawa (Surgical Case Reports)
Abstract Background Small intestinal arteriovenous malformation (AVM) can cause bleeding. Most small intestinal AVMs occur during adulthood, rarely in infancy. We report a case of an infant with hemorrhage due to small intestinal AVM early and recurrently after Kasai portoenterostomy (PE) for biliary atresia (BA). Case presentation A 51-day-old male infant was admitted to our institution for obstructive jaundice. Laparotomic cholangiography revealed BA (IIIb1μ), and Kasai PE was performed at 60 days of age. On postoperative day 17, he developed massive melena and severe anemia. Contrast-enhanced computed tomography (CT) revealed that the jejunum around the PE site was strongly enhanced with enhancing nodules in the arterial phase, and a wide area of the Roux limb wall was slightly enhanced in the venous phase. As melena continued, emergency laparotomy was performed. There were no abnormal macroscopic findings at the PE site except for a clot in the Roux limb 5 cm away from the PE site, and the Roux limb was resected 5 cm. On further investigation, a red spot was detected on the jejunal serosa 30 cm away from the Roux-en-Y anastomosis site. PE and wedge resection for the red spot were performed. Histopathologically, both specimens indicated AVM. He was jaundice-free 65 days after the first surgery. However, at 7 months of age, he developed massive melena again. Contrast-enhanced CT and upper gastrointestinal endoscopy revealed no bleeding lesions. Hemorrhagic scintigraphy showed a slight accumulation at the hepatic hilum prompting an emergency surgery. Intraoperative endoscopy detected a bleeding lesion at the PE site, and the Roux limb was resected (approximately 6 cm). Intraoperative frozen section analysis of the stump of the resected jejunum revealed no abnormal vessels. PE was performed, and permanent section analysis revealed an AVM in the resected jejunum. The postoperative course was uneventful without re-bleeding. Conclusions We experienced a case of recurrent massive bleeding from small intestinal AVM in an infant after surgery for BA. Intraoperative endoscopy and frozen section analysis helped identify the bleeding lesion and perform a complete resection of the small intestinal AVM, even after surgery, in the infant.